Assessing the Extension Service Needs of Credit Officers of Microfinance Banks in Anambra State: Implications for Rural Finance Intermediation - Uchenna , Onugu, Charles; Olabisi , Taiwo Abdulahi; E, Agbasi Obianuju; Kamaldeen, Lawal (Asian Journal of Agriculture and Rural Development, 2015)
The credit officers of Microfinance Banks (MFBs) are key players in rural finance intermediation for economic development. The paper assessed their extension service needs in Anambra State. Thirty-six (36) credit officers drawn from eleven (11) rural based MFBs in Anambra State were the respondents. Data was collected and analyzed using descriptive statistics of simple percentage, frequency table and mean. Three (3) hypotheses were tested with the use of Chi square (x2). The findings of the study revealed that the credit officers are sufficiently knowledgeable about credit extension service delivery. However, they were found not involved in designing, and implementation of effective credit policies for their clients. Also, they are not adequately motivated to carry out their duties. Based on the findings, it was recommended that the board of directors and management of the MFBs should provide capacity building program for credit officers to improve and sustain their knowledge and skills, also they should improve their welfare especially, attractive and encouraging salary, incentives and insurance cover which are paramount to performance.